The other side of the medal: Health issues in retired elite female football players and cues for prevention - Prien, A. H. (Universität Amsterdam, 2020)
Until now, long-term health issues in elite athletes received little attention in sports medicine research. This is an important gap in the literature, as it is known that certain sport-related injuries may predispose elite athletes to adverse long-term outcomes. Particularly scant information is available on long-term health in retired elite female athletes. In order to delay or even prevent long-term health issues in this population, more knowledge about post-career health is needed. Therefore, the aim of my PhD thesis was to analyse the prevalence of long-term health problems and associated risk factors in retired female football players. While chapters 2 and 3 are focused on musculoskeletal health, chapters 4 to 7 investigate cognitive health.